Relationship Between Summer Precipitation in North China and Madden–Julian Oscillation During the Boreal Summer of 2018 - Hao, Lisheng; He, Liye; Ma, Ning; Liang, Sujie; Xie, Jun (Frontiers in Earth Science, 2020)
Based on the data about summer precipitation in North China, tropical MJO (short for Madden-Julian Oscillation) index, and NCEP/NCAR (short for National Centers for Environmental Prediction/National Center for Atmospheric Research) reanalysis data, this paper analyzed the relationship between summer precipitation 2018 in North China and MJO by using multiple statistical methods. Findings indicate that, (1) Summer precipitation in North China is closely related to MJO. During the times when the MJO was in phases 5 and 6, North China had heavy precipitation. (2) The correlation mechanism is mainly: At 850 hPa, when MJO storm clouds move eastward, anticyclonic circulation is excited in the north side of the convection area, thus forming a pair of cyclones and anticyclones. Though MJO storm clouds cannot move northward to higher latitude to have direct impact on the summer precipitation in North China, the anticyclonic circulation on the north side of cyclones during the eastward movement of MJO to phases 5 and 6 can strengthen the water-vapor transfer of southerly wind (corresponding to RMM1) or that of southeast wind (corresponding to RMM2) in summer in North China, thus providing favorable water-vapor conditions for precipitation in North China. At 500 hPa, when MJO moves eastward into phases 5 and 6, the western Pacific subtropical high will move northward to the area near the Korean Peninsula and be strengthened, thus blocking weather systems that come from the west, and facilitating ascending motions in North China. At 200 hPa, MJO-associated convection will generate disturbances at upper troposphere and transmit the impacts of disturbances to downstream areas along the westerly jet waveguide, thus forming a disturbance wave train. When MJO moves eastward into phases 5 and 6, duing to the effect of wave train propagation, disturbances at the height of the 500 hPa pressure will have a positive anomaly near the Korean Peninsula, forming an obvious barotropic structure with 500 hPa subtropical high, which strengthens the blocking to weather systems that come from the west and is favorable to the precipitation in North China. (3) MJO can be used for extended-range forecast of summer precipitation over North China.